Kampanye Sosial tentang Kepedulian terhadap Lansia - Sukina Sukina; Aditya Rahman Yani; Alfian Candra Ayuswantana (Lembaga Pengembangan Kinerja Dosen, 2025)
The growing number of elderly in Indonesia demands more attention from families and communities towards their welfare. The many cases of elderly neglect show a lack of empathy and education regarding the role of families and communities in caring for the elderly. This study designed a social campaign entitled